Waking the 'sleeping giant' or expressing domestic dissent? Mainstreaming Euroscepticism in crisis-stricken Greece. Issue 3 (June 2015) - Verney, Susannah
The surge in support for Eurosceptic parties in the 2014 Euroelections is investigated through a case study of Greece, a country which suffered a dramatic dealignment of its party system after the onset of the Eurozone crisis. The extent to which crisis-era developments represent a rupture is assessed by setting the recent rise of party Euroscepticism in its historical context. Eurobarometer data is used to investigate the relationship between party and popular Euroscepticism and an alternative domestically-driven explanation of causality. The conclusion is that the crisis era has been a game-changer in attitudes towards European integration. The rising vote for Eurosceptic parties is not simply a side-effect of domestic protest. Instead the EU has become a significant electoral target.